Evaluation of “No plastic bag campaign” in Selangor and basic degradation study of plastic bags / Norliana Mohamad Shani - Norliana , Mohamad Shani (2017)
The “No Plastic Bag Day” campaign was triggered by plastic waste issue which is caused by its low degradability rate. However, the significance of the “No Plastic Bag Campaign” currently is still not known. Hence, the objective of this study is to fill the knowledge gap i.e. to conduct test on degradability rates of selected types of plastic bags in different mediums, to determine whether there are differences in the degradation between degradable and non-degradable plastics available in the market, to determine the awareness level of the public in Selangor on the “No Plastic Bag Campaign”, to identify the willingness among the public to shop without plastic bags in Selangor, and to identify the influence of socio-economic background of the respondents on their willingness to shop without plastic bags. Soil burial test were conducted on selected types of plastic bags to determine its degradability by looking at the weight loss, changes on the surface morphology as well as alteration in functional groups of the plastic samples. On the other hand, survey was conducted in Selangor with sample size of 625 people. Non-degradable plastic bag in garden soil has the highest weight loss with 10.2% of weight loss after 120 days. All of the plastic samples showed some changes such as unevenness, roughness, cracks, holes and horizontal notches. In the Fourier transform Infrared (FT-IR) analysis, most of the plastic samples showed increase in the peaks’ intensities through the whole burial period. From the survey it was found that 91.2% of the respondents are aware of the existence of the “No Plastic Bag Day” campaign and 74.1% responded positively to the discontinuation of plastic bag usage. 60% of those who are aware of the campaign are Malays and 61% of those who have received information on the danger of plastic wastes to the environment are female. 76.5% of the respondents have also taken the initiative to reduce the usage of plastic bags. Pearson correlation shows respondents’ willingness to discontinue plastic bag usage to be correlated with their level of education. 50% respondents with higher education background are supportive towards discontinuation of plastic bag usage and 60% without higher education are unsupportive towards it. It can be concluded that there is no significant difference in the degradation of all of the plastic sample and the burial medium did not play a significant role in the degradation rate. Also, majority of the public in Selangor are aware of the “No Plastic Bag Campaign” and are willing to shop without plastic bag. Their willingness to shop without plastic bag is influenced by their education background. Also, respondent’s socio-economic background has an influence on the respondents awareness and willingness to shop without plastic bag.